Contribution of Uttarakhand's cultural heritage in the concept of developed India (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
The aim of this research is to analyse the contribution of Uttarakhand's cultural heritage to the vision of a developed India. Uttarakhand, known as Devbhoomi, is renowned for its rich cultural and historical heritage. This study assesses the economic, social, and cultural development of the state through its cultural heritage, such as religious sites, folk art, traditional architectural styles, and festivals.This research mainly uses two types of methods: primary data collection, which includes interviews with local people and experts, and analysis of secondary sources, which include historical documents, government reports, and previous studies. The focus is also on the preservation and promotion of cultural heritage sites, as well as the potential for tourism and economic development through them. The findings of the research show that the cultural heritage of Uttarakhand has not only strengthened the social and cultural fabric of the state, but is also contributing significantly economically through tourism. Conservation of cultural heritage not only strengthens the cultural identity of the state, but it also plays an important role in the vision of India's development. This research provides policy recommendations for the conservation of cultural heritage of Uttarakhand and highlights the possibilities of sustainable development through them.